PENGARUH PENEMPATAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KEPUASAN KERJA PADA DINAS SUMBER DAYA AIR DAN BINA MARGA PROVINSI SULAWESI TENGGARA - Lilis Aryani Utami; Endro Sukotjo; Sinarwaty Sinarwaty (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This study aims to determine and analyze the effect of work placement and work environment on employee performance mediated by job satisfaction at the Department of Water Resources and Highways of Southeast Sulawesi Province. This research uses survey research design with quantitative research type. The population in this study were all employees in the Department of Water Resources and Highways of Southeast Sulawesi Province of 60 people. The determination of the number of samples in this study was using the census method. The analytical tool used is PLS (Partial Least Square) software.Based on the results of the research conducted, it can be concluded that (1) Job placement has a positive and significant effect on job satisfaction at the Department of Water Resources and Highways of Southeast Sulawesi Province; (2) Work placement has a positive and significant effect on employee performance at the Department of Water Resources and Highways of Southeast Sulawesi Province; (3) The work environment has a positive and significant effect on job satisfaction at the Department of Water Resources and Highways of Southeast Sulawesi Province; (4) The work environment has no significant effect on the performance of employees at the Department of Water Resources and Highways of Southeast Sulawesi Province; (5) Job satisfaction has a positive and significant effect on employee performance at the Department of Water Resources and Highways of Southeast Sulawesi Province; (6) Job placement has a positive and significant effect on employee performance mediated by job satisfaction at the Department of Water Resources and Highways of Southeast Sulawesi Province; and (7) the work environment has a positive and insignificant effect on employee performance mediated by job satisfaction at the Department of Water Resources and Highways of Southeast Sulawesi Province.